Money Attitude and Socio-Demographic Factors as Determinants of University Students’ Spending Behavior in Shah Alam, Malaysia - Jamilah Kamis; Norhasbi Abdul Samad; Lee Siew Pheng; Salina Rasli; Salbiah Hanum Mohd Hajali; Sylvia Ee Fee Peing (Universitas Pamulang, 2021)
ABSTRACTNowadays, uncontrollable spending habit towards Malaysian young generations are becoming progressively. They have a tendency to have less value of money compared to the elder generations in spending their money. Since the cost of living in Malaysia has improved remarkably, the young generations enjoyed spending their money heavenly, therefore Malaysia faced changes in lifestyle and spending trend. This study proposes to investigate the relationship between money attitude and socio-demographic as determinants of college students’ spending behaviours. As such, the correlation between money attitude factors (power-prestige, distrust, retention-time and anxiety) and spending behaviours among Malaysian college students is a topic worthy of further exploration. At the same time, this study also attempts to explore whether college students’ spending behaviours are affected by their socio-demographic factors such as gender, age. The sample of this study consists of 176 students from three different universities in the Shah Alam area i.e University Selangor (UNISEL), University Management Science (MSU) and Universiti Teknologi Malaysia (UiTM). The regression analysis showed that there were only two factors of money attitude (power-prestige, and anxiety) that had a significant effect on spending behaviour among these universities’ students. However, from the analysis, it can be revealed that none of the socio-demographic factors had a significance (more than 0.05) towards the spending behaviour of the students. Thus, age (positive result) is the most influenced factor of the students’ spending behaviour. Consequently, several suggestions have been put forward and hoped that it will assist students in managing their fund effectively